Virtual Galleries as Learning Scaffolds for Promoting Problem-Based Learning - Chrissa Papasarantou; Rene Alimisi; Dimitris Alimisis (MDPI AG, 2023)
Extensive research into the effectiveness of problem-based learning (PBL) in primary and secondary education has been carried out over the past few years. PBL is an appealing, promising, but also challenging educational approach for both students and teachers. To overcome challenges, one of the most popular proposed strategies is to build learning scaffolds that gradually help students to effectively resolve the emerging sub-problems and tasks. Moreover, the massive impact of technology on students' lives, and the transition from in-person to distance teaching (especially during the COVID-19 pandemic) highlights the necessity of using virtual worlds and digital tools to facilitate and amplify collaboration and communication, both synchronously and asynchronously. This paper introduces the virtual galleries method as a scaffold for applying PBL approaches in both physical and distance learning environments, within the field of STEM education. Virtual galleries are perceived as a practice that motivates learners to collaborate, express their ideas on solving a problem, and present them as interactive and immersive experiences, while allowing others (peer-learners and educators) to evaluate the produced solutions. In this context, it is argued that virtual galleries can facilitate PBL by serving as a conceptual framework for scaffolding the learning process, thus enabling the acquisition of new PBL-driven skills.